Customer Discrimination - Leonard, Jonathan S; Levine, David I; Giuliano, Laura (The Review of Economics and Statistics, 2010)
We test for customer discrimination with data from more than 800 retail stores employing over 70,000 individuals matched to census data on the demographics of each store's community. While our tests detect some increase in sales when the workforce more closely resembles potential customers, the effects we find are modest in magnitude. Customer discrimination is neither strong nor pervasive. We find little payoff to matching employee demographics to those of potential customers except when the customers do not speak English.